(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article provides a scientifically grounded analysis of the export dynamics of electrical engineering industry enterprises in Uzbekistan over the period 2017–2025. The study reveals that industrial output increased 9.5 times, reaching 35 trillion UZS, while exports grew 7.4 times to 1,400 million USD. The paper extensively examines global trends in the electrical engineering market, the geography of Uzbekistan’s exports, a quantitative analysis by major product groups, the impact of state policy, and target indicators for 2025–2030. As a conclusion, practical recommendations for enhancing export potential are developed